2003
DOI: 10.1007/s00216-003-2168-7
|View full text |Cite
|
Sign up to set email alerts
|

Cluster calibration in mass spectrometry: laser desorption/ionization studies of atomic clusters and an application in precision mass spectrometry

Abstract: For accurate mass measurements and identification of atomic and molecular species precise mass calibration is mandatory. Recent studies with laser desorption/ionization and time-of-flight analysis of cluster ion production by use of fullerene and gold targets demonstrate the generation of atomic clusters for calibration purposes. Atomic ion results from the Penning trap mass spectrometer ISOLTRAP, in which a carbon cluster ion source has recently been installed, are presented as an application in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Recently, we showed that flower-like AuNPs deposited on the target plate enhance the ionization of peptides [17]. We were curious whether the gold clusters generated by highenergy LDI could be used for the internal calibration of biomolecules such as small peptides or even proteins.…”
Section: Gold Clusters (Au N +/-)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we showed that flower-like AuNPs deposited on the target plate enhance the ionization of peptides [17]. We were curious whether the gold clusters generated by highenergy LDI could be used for the internal calibration of biomolecules such as small peptides or even proteins.…”
Section: Gold Clusters (Au N +/-)mentioning
confidence: 99%
“…Clusters of monoisotopic elements provide simple spectra with many monoisotopic peaks covering the mass range of interest with regular mass spacing. In this work, we discuss the calibration of mass spectra by clusters of red phosphorus, which is already established in our laboratory [6,[10][11][12][13][14][15][16], and compare it with calibration by gold clusters generated directly on the target by laser desorption ionization (LDI)-MS of various materials, including gold foil [17], various types of gold nanoparticles (AuNPs), chloroauric acid (HAuCl 4 ), a mixture of 2-(4-hydroxyphenylazo) benzoic acid and HAuCl 4 [18], and polyvinylpyrrolidone-stabilized AuNPs [19]. Gold clusters provide simple and fast determination of accurate mass compared with common calibration standards, such as peptides or proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIGA-TRAP will carry out absolute mass measurements by using carbon clusters as mass references [83,84]. Clusters up to C þ 23 were produced in pilot measurements with a MALDI-TOF system [63].…”
Section: Absolute Mass Measurements and Heavy-ion Productionmentioning
confidence: 99%
“…In this context, carbon clusters provide the reference mass of choice. 33 The advantages are obvious: a multitude of reference masses all over the nuclear chart are available which are, at most, six atomic mass units away from any nuclide of interest (see Figure 5). Thus, any systematic mass dependent uncertainty which increases with the difference between the measured mass and the reference mass is minimized.…”
Section: Isoltrap: Carbon Clusters In Precision Mass Spectrometrymentioning
confidence: 99%